Identification of a novel phenamacril‐resistance‐related gene by the cDNA‐RAPD method in Fusarium asiaticum. Issue 8 (29th December 2015) - Ren, Weichao; Zhao, Hu; Shao, Wenyong; Ma, Weiwei; Wang, Jianxin; Zhou, Mingguo; Chen, Changjun
Abstract: BACKGROUND: Fusarium asiaticum, a dominant pathogen of Fusarium head blight (FHB) in East Asia, causes huge economic losses. Phenamacril, a novel cyanoacrylate fungicide, has been increasingly applied to control FHB in China, especially where resistance of F. asiaticum against carbendazim is severe. It is important to clarify the resistance‐related mechanisms of F. asiaticum to phenamacril so as to avoid control failures, and to sustain the usefulness of the new product. RESULTS: A novel phenamacril‐resistance‐related gene Famfs1 was obtained by employing the cDNA random amplified polymorphic DNA (cDNA‐RAPD) technique, and was validated by genetic and biochemical assays. Compared with the corresponding progenitors, deletion of Famfs1 in phenamacril‐sensitive or highly phenamacril‐resistant strains caused a significant decrease in effective concentrations inhibiting radial growth by 50% (EC50 value). Additionally, the biological fitness parameters (including mycelial growth under different stresses, conidiation, perithecium formation and virulence) of the deletion mutants attenuated significantly. CONCLUSION: Famfs1 not only was involved in the resistance of F. asiaticum to phenamacril but also played an important role in adaptation of F. asiaticum to the environment. Moreover, our data suggest that the cDNA‐RAPD method can be a candidate technique to clone resistance‐related genes in fungi. © 2015 Society of Chemical Industry